Pengaruh Struktur Modal, Likuiditas Perusahaan Dan Ukuran Perusahaan Terhadap Nilai Perusahaan Dengan Risiko Kredit Sebagai Variabel Mediasi Dalam Industri Perbankan Pada Index LQ45 - Ahmad Khairul Reza (2022)
This research uses secondary quantitative data to determine the effect of capital structure, company liquidity and firm size on firm value with credit risk as a mediating variable. The population of this research are banking companies listed on the Indonesia Stock Exchange in the 2010-2020 period, which amount to 29 banking companies. The data used is the panel data regression method using the eviews version 10 application. The sample selection uses full sampling. The results obtained show that (1) Capital structure has a positive effect on company value, (2) Liquidity has no effect on company value, (3) Company size does not affect company value, (4) Credit risk does not affect company value, (5) Capital structure has a negative effect on credit risk, (6) Liquidity has no effect on credit risk, (7) Company size has a positive effect on credit risk, (8) Credit risk is not proven as an intervening variable in banking companies in Indonesia. Keywords: Capital structure, liquidity, firm size, firm value, credit risk